Diagnóstico sorológico e molecular de agentes transmitidos por artrópodes em aves carnívoras - Sacchi, Ana Beatriz Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Rickettsiales, Haemosporida and Rhizobiales agents cause diseases that affect various animal species, including humans. Carnivorous birds become infested and infected with many species of parasites, including ticks and hemoparasites, and the predation habits favoring transmission and translocation of various etiological agents. The aim of this study was to investigate, using indirect methods (Immunofluorescence - IFAT) and direct methods (blood smears, Real-Time PCR and Conventional PCR) agents of Families Anaplasmataceae (Ehrlichia, Anaplasma, Neorickettsia), Bartonellaceae (Bartonella spp.) and Haemosporida Order (Plasmodium, Haemoproteus and Leucocytozoon) in ectoparasites and blood samples carnivorous birds, performing a phylogenetic study of these agents. Therefore, we collected 121 blood samples and 88 serum samples from birds belonging to the Accipitriformes, Falconiformes, Strigiformes and Cathartiformes Orders, captured in the states of São Paulo and Rio de Janeiro. Regarding the ectoparasites, we collected three larvae and one engorged nymphal Amblyomma ticks of a Rupornis magnirostris in São Paulo. At IFAT for E. chaffeensis and A. phagocytophilum, 03 (3.41%) and 05 (5.68%) samples showed seroreactivity, respectively. Blood smears stained by Giemsa were analyzed and hemoparasites were not found. Regarding the Real-Time PCR (qPCR), in multiplex qPCR for Ehrlichia spp., Anaplasma spp. (groE gene) and Bartonella spp. (nuoG gene) observed 12 samples positive for Anaplasma spp. (9.91%). In conventional PCR-based 16SrRNA gene for Anaplasmataceae and cytochrome B gene for hemosporidia, eight birds were PCR positive for Ehrlichia spp (6.61%, five in PCR for E. chaffeensis and three in PCR for E. canis), three for Haemoproteus spp (2.48%) and Plasmodium spp (0.83%). In phylogenetic analysis, four samples of Ehrlichia spp. positioned on the same branch Ehrlichia identified in wild animals in Brazil and the US human isolate. The ...

Agentes das Ordens Rickettsiales, Haemosporida e Rhizobiales são causadores de enfermidades que acometem várias espécies animais, podendo representar um risco à saúde dos mesmos, inclusive de seres humanos. Aves carnívoras podem infestar-se e infectar-se com muitas espécies de parasitas, incluindose carrapatos e hemoparasitas, sendo os hábitos de predação fatores de favorecimento à transmissão e translocação de diversos agentes etiológicos. O objetivo deste estudo foi pesquisar, por meio de métodos indiretos (Reação de Imunofluorescência Indireta - RIFI) e diretos (esfregaços sanguíneos, PCR em Tempo Real e PCR Convencional) os agentes das Famílias Anaplasmataceae (Ehrlichia, Anaplasma, Neorickettsia), Bartonellaceae (Bartonella spp.) e Ordem Haemosporida (Plasmodium, Haemoproteus e Leucocytozoon) em ectoparasitas e amostras de sangue de aves carnívoras, realizando-se um estudo filogenético dos agentes encontrados. Para tanto, procedeu-se à colheita de 121 amostras de sangue total e 88 amostras de soro de aves pertencentes às Ordens Accipitriformes, Falconiformes, Strigiformes e Cathartiformes, capturadas nos estados de São Paulo e Rio de Janeiro. Em relação aos ectoparasitas, foram recolhidas três larvas e uma ninfa ingurgitada de carrapatos do gênero Amblyomma de um gavião carijó (Rupornis magnirostris) no Estado de São Paulo. Na RIFI para E. chaffeensis e A. phagocytophilum, 03 (3,41%) e 05 (5,68%) amostras apresentaram sororreatividade, respectivamente. Todas as amostras testadas na RIFI para E. canis mostraram-se negativas. Na avaliação de esfregaços sanguíneos corados pelo Giemsa, não foram encontradas estruturas compatíveis com hemoparasitas. Em relação a PCR em Tempo Real (qPCR), não foram encontrados animais PCR positivos para Ehrlichia chaffeensis (gene vlpt) e Anaplasma phagocytophilum (gene msp-2). Na qPCR Multiplex para Ehrlichia spp., Anaplasma spp. (gene groE) e...
Keywords: Ave - Doenças; Ave de rapina; Diagnóstico molecular; Sorodiagnostico; Microorganismos patogenicos; Molecular diagnosis